ISLAMIC EDUCATION and THE LOCAL WISDOM in GLOBALISATION ERA - Usman Usman (Madania: Jurnal Ilmu-Ilmu Keislaman, 2011)
Information technology in the globalization era has made the distance closer and time shorter. In addition, new humanitarianism issues emerge: pluralism, national integration, decentralization, and civil society. These issues are the development of contemporary issues which will inevitably have to face by Islamic education. Here, Islamic education must have the courage to welcome and provide an alternative bid for the solution of these issues. Local wisdom is born as the fruit of the society creativity in order to solve the problems or meet its needs by utilizing human potency and natural resources which exist in its everyday life.